2019
DOI: 10.1088/1741-2552/aaf12e
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of EEG-based brain–computer interface paradigms

Abstract: Advances in brain science and computer technology in the past decade have led to exciting developments in brain–computer interface (BCI), thereby making BCI a top research area in applied science. The renaissance of BCI opens new methods of neurorehabilitation for physically disabled people (e.g. paralyzed patients and amputees) and patients with brain injuries (e.g. stroke patients). Recent technological advances such as wireless recording, machine learning analysis, and real-time temporal resolution have inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
341
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 634 publications
(412 citation statements)
references
References 251 publications
1
341
1
3
Order By: Relevance
“…In non-invasive BCI paradigms, EEG signals are easily collected without brain surgery and commonly used due to their high temporal resolution [4]. The EEG signals have been applied to various types of BCI paradigms such as event-related potential (ERP) [5], movement-related cortical potential (MRCP) [6] and motor imagery (MI) [7]. EEG-based BCI paradigms have been developed for interaction between users and external devices [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In non-invasive BCI paradigms, EEG signals are easily collected without brain surgery and commonly used due to their high temporal resolution [4]. The EEG signals have been applied to various types of BCI paradigms such as event-related potential (ERP) [5], movement-related cortical potential (MRCP) [6] and motor imagery (MI) [7]. EEG-based BCI paradigms have been developed for interaction between users and external devices [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many successful approaches to BCI have been presented in the literature [2,9,10]. While many approaches focus on subject specific models due to high inter-subject variances present in larger populations, a wide array of studies have shown the viability of subject independent (SI) models [2,7,10–13]. Reducing complexity is an important part of emerging consumer grade EEG devices.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, electroencephalography (EEG) is a convenient solution given direct measure of neural activity at milliseconds time precision. Additionally, a wireless EEG headset can make Brain-Computer Interface (BCI) at an individual level simpler to use [18]. EEG has been used as a low-cost brain imaging technique for attention evaluation and training by many researchers [19].…”
Section: Introductionmentioning
confidence: 99%
“…EEG has been used as a low-cost brain imaging technique for attention evaluation and training by many researchers [19]. A number of EEG paradigms have been suggested in connection with attention deficit and attention enhancement [18,19]. In 1976, Lubar and Shouse [20] pioneered the EEG-based neurofeedback training for patients with attention disorders.…”
Section: Introductionmentioning
confidence: 99%